2021
DOI: 10.21203/rs.3.rs-270900/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual Inspection with Acetic Acid (VIA) Positivity Among Female Sex Workers: a Cross-sectional Study Highlighting One-year Experiences in Early Detection of Pre-cancerous and Cancerous Cervical Lesions in Kampala, Uganda

Abstract: Background: Although cervical cancer is preventable, most women in sub-Saharan Africa (SSA) do not receive routine screening and few treatment options exist. Female Sex Workers (FSWs) are among the Ugandan female population at highest risk of acquiring sexually transmitted infections (STIs) including HIV and human papilloma viruses (HPV), the cause of cervical cancer. We report one-year experiences of visual inspection with acetic acid (VIA) positivity among FSWs in the early detection of pre-cancerous and can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Of the 32% VIA positive, 26% were VIA and HIV positive, 1% were ASCUS and HIV negative, and 2% were ASCUS and HIV positive. The findings are consistent with two other studies, one conducted in Kampala, Uganda by Namale, G et al, 2021 (26), who also reported the prevalence of VIA among HIV-positive patients, and another conducted by TASO HIV Clinic at Mulago facility, Kampala (27), also reported 44% of VIA and HIV positive patients. Hence, UNAIDS, 2018 (28) reported that the prevalence of HIVpositive women within the age-15-49 was at 5.4%.…”
Section: Discussionsupporting
confidence: 91%
“…Of the 32% VIA positive, 26% were VIA and HIV positive, 1% were ASCUS and HIV negative, and 2% were ASCUS and HIV positive. The findings are consistent with two other studies, one conducted in Kampala, Uganda by Namale, G et al, 2021 (26), who also reported the prevalence of VIA among HIV-positive patients, and another conducted by TASO HIV Clinic at Mulago facility, Kampala (27), also reported 44% of VIA and HIV positive patients. Hence, UNAIDS, 2018 (28) reported that the prevalence of HIVpositive women within the age-15-49 was at 5.4%.…”
Section: Discussionsupporting
confidence: 91%
“…They argue that VIA screening could be integrated in HIV treatment, thereby addressing and treating abnormal results promptly. Namale et al’.s 18 research in Uganda, however, contradicts these findings. The VIA had low sensitivity in their study, even though administered by trained health workers.…”
Section: Resultsmentioning
confidence: 90%
“…Afzal et al 10 note in their South African study that there are long delays in addressing abnormal Pap smears. Indeed, Namale et al 18 note that, despite their reticence regarding VIA, the same day linkage of the VIA screen-positives to the diagnosis and treatment facility was critical. They call for careful consideration of the feasibility of the ‘screen and treat’ strategy for preventing cervical cancer recommended by the WHO for low-resource countries.…”
Section: Resultsmentioning
confidence: 99%
“…67 Likewise, VIA and Pap test specificity is influenced by HIV infection and its control, probably as a result of their influence on HPV prevalence, as shown in one study that controlled for the presence of HPV. 193 VIA positivity is higher (and its specificity is lower) for WLWH (vs HIV-negative wo men) 182,194,195,196,197,198,199,200 and, among WLWH, for those with lower CD4 counts 183,201 and lack of ART use. 57 Pap test positivity is higher (and its specificity is lower) for WLWH (vs HIV-negative women) 71,202 with higher CD4 cou nts 71,183,193,203,204,205,206,207,208 and lower HIV viral loads.…”
Section: Primary Prevention: Prophylactic Hpv Vaccinationmentioning
confidence: 98%